A Note on Three-Step Iterative Method with Seventh Order of Convergence for Solving Nonlinear Equations: Napassanan Srisarakham, Montri Thongmoon - Team, Support (Thai Journal of Mathematics, 2016)
In this paper, we present a new higher order iterative method for solving nonlinear equations. This method based on a Halley’s iterative method and using predictor-corrector technique. The convergence analysis of this method is discussed. It is established that the new method has convergence order seven. Numerical tests show that the new method is comparable with the well-known existing methods and gives better results.